PRO-INNOVATION ACTIVITIES IN SHAPING THE ORGANIZATIONAL RESILIENCE - Woźniak, Jacek (Management and Administration Journal, 2024)
This work aims to identify factors/activities that may affect the complexity of ensuring organizational resili-ence, as well as the complexity of the importance of ensuring organizational resilience shaped in innovative organizations; and to assess these phenomena in Polish innovative entities. Theoretical methods have been used in the study, i.e., analysis, synthesis, and query of the scientific literature. Inductive inference, as well as elements of deductive inference, have been used. The empirical CAWI survey technique and statistical analysis of quantitative data have also been used. The study used factor analysis, cluster analysis, the analysis of descriptive statistics, and the Kruskal–Wallis test for inde-pendent samples. Studies have shown that the complexity of ensuring organizational resilience (ICAOR indicator) and the complexity of the importance of ensuring organizational resilience (ICIOR indicator) is moderate. Moreover, there is a relatively small “gap” between respondents’ assessment of the level of implementation of factors and activities and the importance of the same factors/activities in the context of ensuring organizational resilience.